2011
DOI: 10.2478/v10194-011-0025-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic influences on ice formation on various water bodies of the Silesian Upland (southern Poland)

Abstract: The aim of the study was to identify patterns of ice-related phenomena on 39 selected anthropogenic water bodies in the Silesian Upland in southern Poland. The core research was conducted in the winter season of 2009/2010, between December and March. Field measurements and observations were conducted every two days during the freezing and thawing phases and every four days at the time of continuous ice cover. Data were interpolated to cover days without observations. Differences in the ice cover phenology on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Often, not only air temperature, determined by local orography, is listed as a factor affecting the ice regime of a lake but also morphometric features, in particular its mean or maximum depth, are listed (Barańczuk and Marchlewicz 2003;Borowiak and Barańczuk 2004;Marszelewski and Skowron 2009;Choiński and Ptak 2012). Moreover, in many research papers authors mention water circulation, groundwater inflows, water residence time and other factors affecting a particular catchment area, such as human impact on the environment and eutrophication processes which affect transparency of the water (Borowiak 2011;Skowron 2011;Solarski et al 2011;Choiński and Ptak 2012;Barańczuk 2018). Some other researchers also deal with the display of ice phenomena in selected areas (Leshkevich and Nghiem 2007;Nazari et al 2009;Nazari and Khanbilvardi 2011;Dorofy et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, not only air temperature, determined by local orography, is listed as a factor affecting the ice regime of a lake but also morphometric features, in particular its mean or maximum depth, are listed (Barańczuk and Marchlewicz 2003;Borowiak and Barańczuk 2004;Marszelewski and Skowron 2009;Choiński and Ptak 2012). Moreover, in many research papers authors mention water circulation, groundwater inflows, water residence time and other factors affecting a particular catchment area, such as human impact on the environment and eutrophication processes which affect transparency of the water (Borowiak 2011;Skowron 2011;Solarski et al 2011;Choiński and Ptak 2012;Barańczuk 2018). Some other researchers also deal with the display of ice phenomena in selected areas (Leshkevich and Nghiem 2007;Nazari et al 2009;Nazari and Khanbilvardi 2011;Dorofy et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ice phenomena on lakes that are not constantly monitored are observed during patrol measurements at certain intervals. Generally, those measurements are carried on one or several lakes simultaneously; the lakes are usual-ly large, deep and flow-through (Bengtsson 1996;Assel 1999;Kuusito 1994;Duguay et al 2006; Karetnikov and Naumenko 2008;Ghanbari et al 2009;Marszelewski and Skowron 2009;Trusewicz et al 2009;Brown and Duguay 2010;Solarski et al 2011; Barańczuk et al 2017;Choiński 2017). Ice cover is systematically observed only on two lakes in the catchment area of the upper Radunia: Lake Ostrzyckie and Lake Raduńskie Górne (the benchmark lakes) ( Barańczuk and Marchlewicz 2003;Borowiak and Barańczuk 2004;Skowron 2011;Choiński et al 2015;Wrzesiński et al 2015…”
Section: Introductionmentioning
confidence: 99%
“…Lake icing has been a subject of interest to many researchers around the world (Assel, Rodionov, 1998;Piliposian, Appleby, 2003;Todd, Mackay, 2003;Duguay et al, 2003;Dibike et al, 2011). In Poland, re-search on ice phenomena in lakes has been conducted for over 50 years (Grześ, 1974;Pasławski, 1982;Sziwa, Jańczak, 2009;Solarski et al, 2011;Ptak, 2013;Choiński et al, 2013;Wrzesiński et al, 2013). Among various aspects of the analyses one of the main is an assessment of impact of climate change on lake regimes in regard to ice phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Although historical observations have not been made at the same place on the lake shore ( Fig. 1), it was demonstrated that when multiple observation records were compared around the lake, no significant difference could be found in the ice regimes recorded at different places around Lake Balaton (Starosolszky, 1988). Stacking resulted in the longest time series of the lake ice regime for Balaton.…”
Section: Historical Observationsmentioning
confidence: 99%